1990
DOI: 10.1007/bf00226238
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the monoterpenes in needles of Picea abies (L.) Karst.

Abstract: The monoterpenes from needles of 47 adult trees of Picea abies (L.) Karst., grown under natural conditions, were studied to get information about the tree-to-tree variation within three adjacent locations and the differences between the locations. For the absolute amounts of the monoterpenes the tree-to-tree variation ranged between 50% and 70%, expressed as the relative coefficient of variation. All three populations showed similar variations. When looking for different genotypes, at each location two groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 18 publications
4
18
0
Order By: Relevance
“…In the present study, the variation may be attributed to abrupt changes in climatic conditions prevailing in the mainland of Albania. The decrease in needle resin yield from autumn to spring is also supported by other previous investigations (Guenther, 1952;Schonwitz et al, 1990). More than sixty compounds were detected and identified in the needle oleoresins of A. alba, rep resenting approximately 92-96% of the oleoresin (Table III).…”
Section: Needle Oleoresinsupporting
confidence: 87%
“…In the present study, the variation may be attributed to abrupt changes in climatic conditions prevailing in the mainland of Albania. The decrease in needle resin yield from autumn to spring is also supported by other previous investigations (Guenther, 1952;Schonwitz et al, 1990). More than sixty compounds were detected and identified in the needle oleoresins of A. alba, rep resenting approximately 92-96% of the oleoresin (Table III).…”
Section: Needle Oleoresinsupporting
confidence: 87%
“…Monoterpene composition is quite stable in mature needles, but the absolute amount of individual and total monoterpenes fluctuate during the seasons (Schonwitz et al, 1990), and this was also observed in our study. In the present study the greatest differences were found in the concentrations of 3-carene, a-pinene, /?-pinene + sabinene, myrcene, tricyclene and total monoterpenes between seasons.…”
Section: Total Phenolicssupporting
confidence: 86%
“…The elevated levels of monoterpenes and sesquiterpenes after MeJA spraying peaked 15 d after treatment but declined to control levels rapidly after that, probably as a result of volatilization or catabolism. Seasonal declines of monoterpene levels in Norway spruce foliage have been noted previously (Schö nwitz et al, 1990b).…”
Section: Induced Terpene Accumulation In Needles Is Much Lower Than Imentioning
confidence: 59%